answersLogoWhite

0


Best Answer

are you in Kindergarten of course one plus one will equal 2

User Avatar

Wiki User

โˆ™ 2012-01-06 06:08:54
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides
๐Ÿ““
See all Study Guides
โœ๏ธ
Create a Study Guide

Add your answer:

Earn +20 pts
Q: 2 cot x plus 1 plus -1?
Write your answer...
Submit
Related questions

2 cot x plus 1 equals -1?

2 cot(x) + 1 = -1 2 cot(x) = -2 cot(x) = -1 cos(x)/sin(x) = -1 cos(x) = - sin(x) x = 135°, 315°, 495°, ... another one every 180 degrees


What is cot x?

Cot x is 1/tan x or cos x / sin x or +- sqrt cosec^2 x -1


How do you prove that (1 plus cotx)2-2cotx 1(1-cos)(1 plus cos)?

Manipulate normally, noting:cot x = cos x / sin xcos² x + sin² x = 1 → sin²x = 1 - cos² xa² - b² = (a + b)(a - b)1 = 1²ab = baa/(bc) = a/b/c(1 + cot x)² - 2 cot x = 1² + 2 cot x + cot² x - 2 cot x= 1 + cot² x= 1 + (cos x / sin x)²= 1 + cos² x / sin² x= 1 + cos² x / (1 - cos² x)= ((1 - cos² x) + cos² x)/(1 - cos² x)= 1/(1² - cos² x)= 1/((1 + cos x)(1 - cos x))= 1/(1 - cos x)/(1 + cos x)QED.


Prove identity cos 2xcot2 x-1cot2 x1?

the questions is 2x=(cot^2 x-1)/(cot^2 x+1)


Cos2x equals 1 minus tan squared x divide by1 plus tan squared x?

The Answer is 1 coz, 1-Tan squarex = Cot square X. So cot square x divided cot square x is equal to 1


What is the second derivative of ln(tan(x))?

f'(x) = 1/tan(x) * sec^2(x) where * means multiply and ^ means to the power of. = cot(x) * sec^2(x) f''(x) = f'(cot(x)*sec^2(x) + cot(x)*f'[sec^2(x)] = -csc^2(x)*sec^2(x) + cot(x)*2tan(x)sec^2(x) = sec^2(x) [cot(x)-csc^2(x)] +2tan(x)cot(x) = sec^2(x) [cot(x)-csc^2(x)] +2


Cotangent squared plus one equals cosecant squared?

yes 1 + cot x^2 = csc x^2


Second derivative of cosecx?

d/dx cosec(x) = - cosec(x) * cot(x) so the second derivative or d(d/dx)/dx cosec(x) = [- cosec(x) * d/dx cot(x)] + [ - d/dx cosec(x) * cot(x)] = [- cosec(x) * -cosec^2(x)] + [ - (- cosec(x) * cot(x)) * cot(x)] = cosec(x) * cosec^2(x) + cosec(x)*cot^2(x) = cosec(x) * [cosec^2(x) + cot^2(x)].


What is the derivative of x equals cot2 divided by t?

Assuming you want dx/dt and that the equation is x = cot(2) / t (i.e. cot(2) is a constant) we can use the power rule. First, we rewrite it: cot(2)/t = cot(2) * t-1 thus, by the power rule: dx/dt = (-1) cot(2) * t-1 -1 = - cot(2) * t-2= = -cot(2)/t2


Csc squared divided by cot equals csc x sec. can someone make them equal?

cot(x)=1/tan(x)=1/(sin(x)/cos(x))=cos(x)/sin(x) csc(x)=1/sin(x) sec(x)=1/cos(x) Therefore, (csc(x))2/cot(x)=(1/(sin(x))2)/cot(x)=(1/(sin(x))2)/(cos(x)/sin(x))=(1/(sin(x))2)(sin(x)/cos(x))=(1/sin(x))*(1/cos(x))=csc(x)*sec(x)


How do you find cot on your Texas Instruments TI-83 Plus calculator?

The TI-83 does not have the cot button, however, if you type 1/tan( then this will work the same as the cot since cot=1/tan. The other way to do this is to type (cos(x))/(sin(x)) where x is the angle you're looking for. This works because cot=cos/sin


What is the cotangent of x in terms of cosecant of x?

cot(x) = sqrt[cosec^2(x) - 1]


What is the answer to cot squared x - tan squared x equals 0?

cot2x-tan2x=(cot x -tan x)(cot x + tan x) =0 so either cot x - tan x = 0 or cot x + tan x =0 1) cot x = tan x => 1 / tan x = tan x => tan2x = 1 => tan x = 1 ou tan x = -1 x = pi/4 or x = -pi /4 2) cot x + tan x =0 => 1 / tan x = -tan x => tan2x = -1 if you know about complex number then infinity is the solution to this equation, if not there's no solution in real numbers.


How do you factor x squared plus 2 x plus 1?

(x + 1)(x + 1) or (x + 1)2


What is x plus 1 plus x minace 2?

x+1+x-2=2x-1


Can you simplify 1-cot x?

csc^2x+cot^2x=1


What is 1 plus 1 x 2 plus 3 x 42 plus 10 x 5?

1 plus 1 x 2 plus 3 x 42 plus 10 x 5 = 1 + 2 + 126 + 50 = 179


How do you simplify sec x cot x?

sec(x)*cot(x) = (1/cos(x))*(cos(x)/sin(x)) = (1/sin(x)) = csc(x)


Express sine in terms of cotangent?

sin(x) = [1 + cot^2(x)]^-0.5


How do you solve csc x sin x equals cos x cot x plus?

Suppose csc(x)*sin(x) = cos(x)*cot(x) + y then, ince csc(x) = 1/sin(x), and cot(x) = cos(x)/sin(x), 1 = cos(x)*cos(x)/sin(x) + y so y = 1 - cos2(x)/sin(x) = 1 - [1 - sin2(x)]/sin(x) = [sin2(x) + sin(x) - 1]/sin(x)


5x plus 4 x-2 -2x 2 x-1 plus 3 x plus 2?

The equation 5X plus 4X-2-2 times2 X-1 plus 3 X plus 2 equals 2. This is a math problem.


What is the LCM of xy(x plus 1) and x(x plus 2)?

xy(x + 1)(x + 2)


5x plus 4 x-2 -2x 2 x-1 plus 3 x plus 2 math college?

The equation 5X plus 4 X-2 -2X 2 X-1 plus3 X plus 2 equals to 2. This is college math.


What is X squared plus x plus x plus one?

It is the same as: x^2 +2x +1 and it is (x+1)(x+1) when factored


What is the answer to x - 2 2x plus 1 or 10 -2x plus 2 equals?

2 plus 1-x divided by.